Cutting edge zirconium oxide surface treatment method

By using a multi-step zirconium oxide surface treatment method on the ceramic blade, it is filled with SiC, TiC and CrN powder to enhance the toughness and strength of the ceramic blade, solve the problem of easy fracture of the ceramic blade, and significantly improve its durability.

CN119350056APending Publication Date: 2025-01-24YAAN HENGCHENG PRECISION TOOL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310910151.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing ceramic knives are prone to collapse or breaking due to excessive force during use, mainly because the slip system of the ceramic material is very small, which causes breaking before slippage occurs.

Method used

The surface treatment method of blade oxidation is used to prepare oxide -based ceramic suspension with ultra -fine oxide powder powder and other additives. The surface toughness and strength of the blade.

Benefits of technology

By sintering and filling the hard granules in stages, the toughness and strength of the ceramic blade is enhanced, the expansion and stress concentration of cracks are reduced, and the durability and service life of the ceramic knife significantly improves the durability and service life of the ceramic knife.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004354880520000071
    Figure BDA0004354880520000071
Patent Text Reader

Abstract

The invention discloses a blade zirconia surface treatment method, and belongs to the technical field of ceramic cutters. The blade zirconium oxide surface treatment method comprises the following steps: taking superfine zirconium oxide powder as a raw material, and adding acrylamide, N, N-methylene bisacrylamide, ammonium persulfate, tetramethylethylenediamine, a dispersing agent and ammonia water to prepare a zirconium oxide-based ceramic suspension with the solid phase content of 52%. In order to solve the problem that an existing ceramic knife is broken or fractured once overexertion occurs in the using process, two surfaces of a crack are connected through a bridging unit, closing stress is generated between two interfaces, and the upper surface and the lower surface of an expansion crack are nailed by complete particles within a certain distance behind the tip of the crack; and the stress intensity factor of the tip of the crack is reduced by preventing the crack from opening, so that the plastic deformation of the particle in the toughening and crack expansion process is realized, the driving force of macroscopic crack expansion is consumed, and the surface toughness and strength of the ceramic blade can be enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic cutters, in particular to a method for treating the surface of a cutting edge zirconium oxide. Background Art

[0002] Most ceramic knives are made of a nano material called "zirconia". Zirconia + alumina powder is pressed into a knife blank under a weight of 300 tons and a mold, sintered at 2000 degrees Celsius, and then diamond polished and equipped with a handle to make a finished ceramic knife. Ceramic blades are a new type of blade made using high-tech nanotechnology. They are more than ten times sharper than steel knives. Therefore, ceramic knives have the characteristics of high hardness, high density, high temperature resistance, anti-magnetization, and anti-oxidation.

[0003] In existing ceramic materials, the bonds between atoms are covalent bonds and ionic bonds. Covalent bonds have obvious directionality and saturation, while the repulsion is very large when ions of the same sign approach each other. Therefore, ceramics mainly composed of ionic crystals and covalent crystals have very few slip systems and generally break before slip occurs. Therefore, if excessive force is applied during the use of ceramic knives, chipping or fracture will occur. Therefore, the existing needs are not met, and a zirconia surface treatment method for blades is proposed. Summary of the invention

[0004] The object of the present invention is to provide a method for treating the surface of a blade zirconia, which has XXXX and can solve the problems in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for treating the surface of a blade zirconia, comprising the following steps:

[0006] Step 1: Using ultrafine zirconium oxide powder as raw material, adding acrylamide, N,N-methylenebisacrylamide, ammonium persulfate, tetramethylethylenediamine, dispersant and ammonia water to prepare a zirconium oxide-based ceramic suspension with a solid content of 52%;

[0007] Step 2: Inject the prepared blank slurry into the porous mold. Due to the water absorption of the porous mold, the slurry is absorbed by the mold on the side close to the mold wall to form a uniform mud layer, which thickens with time. When the required thickness is reached, the excess mud is poured out. Finally, the mud layer continues to dehydrate and shrink and separates from the mold. After being taken out of the mold, it is a blank.

[0008] Step 3: Place the ceramic knife blank in a vacuum sintering furnace, pre-sinter it to 1000-1200°C at a heating rate of 0.5-1°C / min, and keep it at 1000-1200°C for 1-2 hours. After the knife blank is sintered and shaped, take it out and place it in a bellows to cool the surface of the knife blank through the refrigeration bellows;

[0009] Step 4: The glaze on the surface of the knife blank is cooled. Due to thermal expansion and contraction, the glaze shrinks rapidly, but the temperature of the internal body drops very little at this time. In this way, the glaze will be subjected to the tensile force of the body to prevent the glaze from shrinking. When the tensile stress on the surface of the glaze layer exceeds the strength of the glaze layer, micro cracks will appear on the knife blank;

[0010] Step 5: Put the knife blank with horizontal rows into the mixed powder of SiC, TiC and CrN, and stir it by using a drum stirring device for 15 to 25 minutes. Take out the knife blank and put it back into the vacuum sintering furnace, and then heat it to 1450 to 1600°C at a heating rate of 1.5 to 3°C / min, keep it at 1450 to 1600°C for 2 to 4 hours, and finally cool it in the furnace to obtain a finished ceramic knife;

[0011] Step 6: Place the ceramic knife in a soft polishing liquid to remove the raised powder particles on the surface, and then use traditional mechanical polishing to grind and polish the entire surface of the knife body. After the polishing work is completed, sharpen the ceramic knife.

[0012] Preferably, in step 2, the thickness of the knife blank is 1.1 to 1.3 mm.

[0013] Preferably, in step three, the temperature of the bellows is controlled at 0-5°C, and the cooling time is 15-20s.

[0014] Preferably, in step 4, the depth of the microcracks is between 0.35 and 0.4 mm.

[0015] Preferably, in step five, the particle diameters of SiC, TiC and CrN are between 0.1 and 0.3 μm.

[0016] Preferably, in step six, the cutting thickness is 0.35 to 0.5 mm.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. The present invention divides the sintering of the knife blank into two steps. After the first stage of sintering is completed, the surface of the knife blank is cooled. The glaze surface on the surface of the knife blank is cooled. Due to thermal expansion and contraction, the glaze surface shrinks rapidly. However, at this time, the temperature of the internal body drops very little, so the glaze surface is subjected to the tensile force of the body to prevent the glaze surface from shrinking. When the tensile stress on the surface of the glaze layer exceeds the strength of the glaze layer, micro cracks are generated in the knife blank. Subsequently, SiC, TiC and CrN powders are filled into the cracks on the surface of the knife blank. SiC, TiC and CrN are used as bridging agents to perform a two-stage sintering process. When the dispersed phase particles and the matrix phase Residual compressive stress is generated around the interface. When the crack encounters dispersed particles, the original direction of advance will be reversed. Crack bridging usually occurs at the crack tip, relying on the bridging unit to connect the two surfaces of the crack and generate closing stress between the two interfaces. The upper and lower surfaces of the extended crack are pinned by intact particles within a certain distance behind the crack tip. The particles reduce the stress intensity factor at the crack tip by preventing the crack from opening, thereby achieving toughening. The crack propagation process causes plastic deformation of the particles, which consumes the driving force for macro crack propagation, thereby enhancing the surface toughness and strength of the ceramic blade. DETAILED DESCRIPTION

[0019] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0020] Embodiment 1:

[0021] A method for treating the surface of a blade of zirconium oxide comprises the following steps:

[0022] Step 1: Using ultrafine zirconium oxide powder as raw material, adding acrylamide, N,N-methylenebisacrylamide, ammonium persulfate, tetramethylethylenediamine, dispersant and ammonia water to prepare a zirconium oxide-based ceramic suspension with a solid content of 52%;

[0023] Step 2: Inject the prepared blank slurry into the porous model. Due to the water absorption of the porous model, the slurry is absorbed by the mold on the side close to the mold wall to form a uniform mud layer, which thickens with time. When the required thickness is reached, pour out the excess mud. Finally, the mud layer continues to dehydrate and shrink and separates from the model. After being taken out of the model, it is a blank. The thickness of the knife blank is 1.1mm;

[0024] Step 3: Place the ceramic knife blank in a vacuum sintering furnace, pre-sinter it to 1200°C at a heating rate of 0.5°C / min, and keep it at 1200°C for 2 hours. After the knife blank is sintered and shaped, take it out and place it in a bellows. The surface of the knife blank is cooled by the refrigeration bellows. The bellows temperature is controlled at 5°C and the cooling time is 20 seconds.

[0025] Step 4: The glaze on the surface of the knife blank is cooled. Due to thermal expansion and contraction, the glaze shrinks rapidly, but the temperature of the internal body drops little at this time, so the glaze will be subjected to the tensile force of the body to prevent the glaze from shrinking. When the tensile stress on the surface of the glaze layer exceeds the strength of the glaze layer, micro-cracks will appear on the knife blank, and the depth of the micro-cracks is 0.35mm;

[0026] Step 5: Put the knife blank with horizontal rows into the mixed powder of SiC, TiC and CrN, the particle diameter of SiC, TiC and CrN is 0.1μm, use the drum stirring equipment to stir, the stirring time is 25min, take out the knife blank and put it back into the vacuum sintering furnace, then heat it to 1600℃ at a heating rate of 1.5℃ / min, keep it at 1450℃ for 4 hours, and finally cool it in the furnace to obtain the finished ceramic knife;

[0027] Step 6: Place the ceramic knife in a soft polishing liquid to remove the raised powder particles on the surface, and then use traditional mechanical polishing to grind and polish the entire surface of the knife body. After the polishing work is completed, sharpen the ceramic knife with a blade thickness of 0.5mm.

[0028] Embodiment 2:

[0029] A method for treating the surface of a blade of zirconium oxide comprises the following steps:

[0030] Step 1: Using ultrafine zirconium oxide powder as raw material, adding acrylamide, N,N-methylenebisacrylamide, ammonium persulfate, tetramethylethylenediamine, dispersant and ammonia water to prepare a zirconium oxide-based ceramic suspension with a solid content of 52%;

[0031] Step 2: Inject the prepared blank slurry into the porous model. Due to the water absorption of the porous model, the slurry is absorbed by the mold on the side close to the mold wall to form a uniform mud layer, which thickens with time. When the required thickness is reached, pour out the excess mud. Finally, the mud layer continues to dehydrate and shrink and separates from the model. After being taken out of the model, it is a blank. The thickness of the knife blank is 1.1mm;

[0032] Step 3: Place the ceramic knife blank in a vacuum sintering furnace, pre-sinter it to 1000°C at a heating rate of 1°C / min, and keep it at 1000°C for 1h. After the knife blank is sintered and shaped, take it out and place it in a bellows. The surface of the knife blank is cooled by the refrigeration bellows. The bellows temperature is controlled at 0°C and the cooling time is 15s.

[0033] Step 4: The glaze on the surface of the knife blank is cooled. Due to thermal expansion and contraction, the glaze shrinks rapidly, but the temperature of the internal body drops little at this time, so the glaze will be subjected to the tensile force of the body to prevent the glaze from shrinking. When the tensile stress on the surface of the glaze layer exceeds the strength of the glaze layer, micro-cracks will appear on the knife blank, and the depth of the micro-cracks is 0.4mm;

[0034] Step 5: Put the knife blank with horizontal rows into the mixed powder of SiC, TiC and CrN, the particle diameter of SiC, TiC and CrN is 0.1μm, use the drum stirring equipment to stir, the stirring time is 15min, take out the knife blank and put it back into the vacuum sintering furnace, then heat it to 1450℃ at a heating rate of 3℃ / min, keep it at 1600℃ for 2 hours, and finally cool it in the furnace to obtain the finished ceramic knife;

[0035] Step 6: Place the ceramic knife in a soft polishing liquid to remove the raised powder particles on the surface, and then use traditional mechanical polishing to grind and polish the entire surface of the knife body. After the polishing work is completed, sharpen the ceramic knife with a blade thickness of 0.35mm.

[0036] Embodiment 3:

[0037] A method for treating the surface of a blade of zirconium oxide comprises the following steps:

[0038] Step 1: Using ultrafine zirconium oxide powder as raw material, adding acrylamide, N,N-methylenebisacrylamide, ammonium persulfate, tetramethylethylenediamine, dispersant and ammonia water to prepare a zirconium oxide-based ceramic suspension with a solid content of 52%;

[0039] Step 2: Inject the prepared blank slurry into the porous mold. Due to the water absorption of the porous mold, the slurry is absorbed by the mold on the side close to the mold wall to form a uniform mud layer, which thickens with time. When the required thickness is reached, pour out the excess mud. Finally, the mud layer continues to dehydrate and shrink and separates from the mold. After being taken out of the mold, it is a blank. The thickness of the knife blank is 1.3mm.

[0040] Step 3: Place the ceramic knife blank in a vacuum sintering furnace, pre-sinter it to 1200°C at a heating rate of 0.5°C / min, and keep it at 1200°C for 2 hours. After the knife blank is sintered and shaped, take it out and place it in a bellows. The surface of the knife blank is cooled by the refrigeration bellows. The bellows temperature is controlled at 5°C and the cooling time is 20 seconds.

[0041] Step 4: The glaze on the surface of the knife blank is cooled. Due to thermal expansion and contraction, the glaze shrinks rapidly, but the temperature of the internal body drops little at this time, so the glaze will be subjected to the tensile force of the body to prevent the glaze from shrinking. When the tensile stress on the surface of the glaze layer exceeds the strength of the glaze layer, micro-cracks will appear on the knife blank, and the depth of the micro-cracks is 0.4mm;

[0042] Step 5: Put the knife blank with horizontal rows into the mixed powder of SiC, TiC and CrN, the particle diameter of SiC, TiC and CrN is 0.3μm, use the drum stirring equipment to stir, the stirring time is 25min, take out the knife blank and put it back into the vacuum sintering furnace, then heat it to 1600℃ at a heating rate of 1.5℃ / min, keep it at 1450℃ for 4 hours, and finally cool it in the furnace to obtain the finished ceramic knife;

[0043] Step 6: Place the ceramic knife in a soft polishing liquid to remove the raised powder particles on the surface, and then use traditional mechanical polishing to grind and polish the entire surface of the knife body. After the polishing work is completed, sharpen the ceramic knife with a blade thickness of 0.5mm.

[0044] Embodiment 4:

[0045] A method for treating the surface of a blade of zirconium oxide comprises the following steps:

[0046] Step 1: Using ultrafine zirconium oxide powder as raw material, adding acrylamide, N,N-methylenebisacrylamide, ammonium persulfate, tetramethylethylenediamine, dispersant and ammonia water to prepare a zirconium oxide-based ceramic suspension with a solid content of 52%;

[0047] Step 2: Inject the prepared blank slurry into the porous model. Due to the water absorption of the porous model, the slurry is absorbed by the mold on the side close to the mold wall to form a uniform mud layer, which thickens with time. When the required thickness is reached, pour out the excess mud. Finally, the mud layer continues to dehydrate and shrink and separates from the model. After being taken out of the model, it is a blank. The thickness of the knife blank is 1.1mm;

[0048] Step 3: Place the ceramic knife blank in a vacuum sintering furnace, pre-sinter it to 1200°C at a heating rate of 0.5°C / min, and keep it at 1200°C for 2 hours. After the knife blank is sintered and shaped, take it out and place it in a bellows. The surface of the knife blank is cooled by the refrigeration bellows. The bellows temperature is controlled at 5°C and the cooling time is 20 seconds.

[0049] Step 4: The glaze on the surface of the knife blank is cooled. Due to thermal expansion and contraction, the glaze shrinks rapidly, but the temperature of the internal body drops little at this time, so the glaze will be subjected to the tensile force of the body to prevent the glaze from shrinking. When the tensile stress on the surface of the glaze layer exceeds the strength of the glaze layer, micro-cracks will appear on the knife blank, and the depth of the micro-cracks is 0.35mm;

[0050] Step 5: Put the knife blank with horizontal rows into the mixed powder of SiC and TiC, the particle diameter of SiC, TiC and CrN is 0.1μm, and stir it by using a drum stirring device for 25min. Take out the knife blank and put it back into the vacuum sintering furnace, and then heat it to 1600℃ at a heating rate of 1.5℃ / min, keep it at 1450℃ for 4 hours, and finally cool it in the furnace to obtain the finished ceramic knife;

[0051] Step 6: Place the ceramic knife in a soft polishing liquid to remove the raised powder particles on the surface, and then use traditional mechanical polishing to grind and polish the entire surface of the knife body. After the polishing work is completed, sharpen the ceramic knife with a blade thickness of 0.5mm.

[0052] Combined with Examples 1-4, the performance test results of the prepared ceramic knife are as follows:

[0053]

[0054] As can be seen from the table above, the sintering of the knife blank is divided into two processes. After the first stage of sintering is completed, the surface of the knife blank is cooled. The glaze on the surface of the knife blank is cooled. Due to thermal expansion and contraction, the glaze shrinks rapidly, but the temperature of the internal body drops very little at this time. In this way, the glaze will be subjected to the tensile force of the body to prevent the glaze from shrinking. When the tensile stress on the surface of the glaze layer exceeds the strength of the glaze layer, micro cracks will appear in the knife blank. Subsequently, SiC, TiC and CrN powders are filled into the cracks on the surface of the knife blank. SiC, TiC and CrN are used as bridging agents to perform a two-stage sintering operation. When the dispersed phase particles and the matrix phase Residual compressive stress is generated around the interface. When the crack encounters dispersed particles, the original direction of advance will be reversed. Crack bridging usually occurs at the crack tip, relying on the bridging unit to connect the two surfaces of the crack and generate closing stress between the two interfaces. The upper and lower surfaces of the extended crack are pinned by intact particles within a certain distance behind the crack tip. The particles reduce the stress intensity factor at the crack tip by preventing the crack from opening, thereby achieving toughening. The crack propagation process causes plastic deformation of the particles, which consumes the driving force for macro crack propagation, thereby enhancing the surface toughness and strength of the ceramic blade.

[0055] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0056] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for treating the surface of a blade of zirconium oxide, characterized in that: The steps include: Step 1: Using ultrafine zirconium oxide powder as raw material, adding acrylamide, N,N-methylenebisacrylamide, ammonium persulfate, tetramethylethylenediamine, dispersant and ammonia water to prepare a zirconium oxide-based ceramic suspension with a solid content of 52%; Step 2: Inject the prepared blank slurry into the porous mold. Due to the water absorption of the porous mold, the slurry is absorbed by the mold on the side close to the mold wall to form a uniform mud layer, which thickens with time. When the required thickness is reached, the excess mud is poured out. Finally, the mud layer continues to dehydrate and shrink and separates from the mold. After being taken out of the mold, it is a blank. Step 3: Place the ceramic knife blank in a vacuum sintering furnace, pre-sinter it to 1000-1200°C at a heating rate of 0.5-1°C / min, and keep it at 1000-1200°C for 1-2 hours. After the knife blank is sintered and shaped, take it out and place it in a bellows to cool the surface of the knife blank through the refrigeration bellows; Step 4: The glaze on the surface of the knife blank is cooled. Due to thermal expansion and contraction, the glaze shrinks rapidly, but the temperature of the internal body drops very little at this time. In this way, the glaze will be subjected to the tensile force of the body to prevent the glaze from shrinking. When the tensile stress on the surface of the glaze layer exceeds the strength of the glaze layer, micro cracks will appear on the knife blank; Step 5: Put the knife blank with horizontal rows into the mixed powder of SiC, TiC and CrN, and stir it by using a drum stirring device for 15 to 25 minutes. Take out the knife blank and put it back into the vacuum sintering furnace, and then heat it to 1450 to 1600°C at a heating rate of 1.5 to 3°C / min, keep it at 1450 to 1600°C for 2 to 4 hours, and finally cool it in the furnace to obtain a finished ceramic knife; Step 6: Place the ceramic knife in a soft polishing liquid to remove the raised powder particles on the surface, and then use traditional mechanical polishing to grind and polish the entire surface of the knife body. After the polishing work is completed, sharpen the ceramic knife.

2. The method for treating the surface of a blade of zirconium oxide according to claim 1, characterized in that: In the step 2, the thickness of the knife blank is 1.1-1.3 mm.

3. The method for treating the surface of a blade of zirconium oxide according to claim 1, characterized in that: In the step 3, the temperature of the bellows is controlled at 0-5°C, and the cooling time is 15-20s.

4. The method for treating the surface of a blade of zirconium oxide according to claim 1, characterized in that: In the step 4, the depth of the microcracks is between 0.35 and 0.4 mm.

5. The method for treating the surface of a blade of zirconium oxide according to claim 1, characterized in that: In the step 5, the particle diameters of SiC, TiC and CrN are between 0.1 μm and 0.3 μm.

6. The method for treating the surface of a blade of zirconium oxide according to claim 1, characterized in that: In the step six, the blade thickness is 0.35 to 0.5 mm.

Citation Information

Patent Citations

  • Glazing method for reducing glaze shrinkage defects on ceramic surfaces

    CN110668845A

  • Preparation method of ceramic rock plate and the ceramic rock plate

    CN111704450A

  • Zirconia toughened alumina cutting tool and preparation method therefor

    WO2022165948A1